Performance evaluation of an electrometer system for ion and aerosol charge measurements - Intra P. (2014)
An aerosol electrometer system for measuring ion and aerosol charge using electrostatic detection technique was developed and presented. It consists of a size-selective inlet, a particle charger, an ion trap, a Faraday cup, an electrometer, and a data acquisition and processing system. In this system, an aerosol sample first passes through the size-selective inlet to remove particles outside the measurement size range based on their aerodynamic diameter, and then passes through the unipolar corona charger that sets a charge on the particles and enters the ion trap to remove the free ions. After the ion trap, the charged particles then enter the Faraday cup electrometer for measuring ultra low current of about 1 pA induced by ion and aerosol charge collected on the filter in Faraday cup corresponding to the number concentration of ion and aerosol. Signal current is then recorded and processed by a data acquisition system. Finally, the detailed description of the operating principle of the system as well as the preliminary experimental testing results of ion and aerosol charge measurements were also introduced and discussed. © 2011 Korean Institute of Chemical Engineers, Seoul, Korea.